Feasibility study based on economic perspective of cobalt nanoparticle synthesis with chemical reduction method - Nandatamadini, Fira; Karina, iSuci; Nandiyanto, Asep Bayu Dani; Ragadhita, Risti (جامعة الوادي - university of el oued, 2019)
Cobalt nanoparticle powder is synthesized by a chemical reduction method. In short, it is synthesized through reduction of cobalt ions that are dissolved in aqueous solution by Boronrelated solution with cationic surfactant. Cobalt nanoparticles have many applications, especially in the field of engineering. The successful project for the production of cobalt nanoparticles will produce opportunities that make it possible to advance technology in developing countries. For this reason, a feasibility study for the synthesis of cobalt powder nanoparticles is needed. This project has estimated ideal conditions for worst cases that will occur in production by adding several parameters: raw materials and sales. Evaluation of this feasibility study is using two parameters, which are economic analysis and evaluation techniques, including Gross Profit Margin (GPM), Cumulative Net Present Value (CNPV), Break-Even Point (BEP), Payback Period (PBP) this parameter to show potential profitability for the project. The IRR value of this project that it is not very promising, but all evaluations with various parameters have a positive impact. The project also uses the method of reducing metal salt an easy and the total cost of purchasing relatively inexpensive equipment will provide benefits in the project, and investors will attract this project.
Article Article
Keywords: Cobalt nanoparticles, Reduction, Mass balance, Economic evaluation, Feasibility study